Beginnings of Peruvian orthopaedics and traumatology in the story of Ricardo Palma’s «Brazo de plata» - Linares Huayhua, Nadia Elizabeth (2020)
This article will analyse the stories «Brazo de plata» and «Amor de madre», texts belonging to Ricardo Palma. We will emphasise the character known as «Brazo de plata», the 23rd viceroy of Peru, because through the amputation to which he was subjected and the decision to have a prosthesis made to replace his right arm, the historical context of orthopaedics and traumatology in the world and the beginnings of this medical speciality in our country are made known.